(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
A course management system (CMS) is a software program or integrated platform thatcontains a series of web-based tools to support a number of activities and course managementprocedures (Severson, 2004). Examples of Course Management Systems are Blackboard,WebCT, eCollege, Moodle, Desire2Learn, Angel, etc. An argument for the adoption of e- learning environments using CMSs is the flexibility of such environments when reaching out topotential learners in remote areas where brick and mortar institutions are non-existent. It is also believed that e-learning environments can have potential added learning benefits and can improve students‘ and educators‘ self-regulation skills, in particular their metacognitive skills. In spite of this potential to improve learning by means of using a CMS for the delivery of e-learning, the features and functionalities that have been built into these systems are often underutilized. As a consequence, the created learning environments in CMSs do not adequatelyscaffold learners to improve their self- regulation skills. In order to support the improvement of both the learners‘ subject matter knowledge and learning strategy application, the e-learning environments within CMSs should be designed to address learners‘ diversity in terms of learning styles, prior knowledge, culture, and self-regulation skills. Self-regulative learners are learners who can demonstrate ‗personal initiative, perseverance and adaptive skill in pursuing learning‘ (Zimmerman, 2002). Self-regulation requires adequate monitoring strategies and metacognitive skills. The created e-learning environments should encourage the application of learners‘ metacognitive skills by prompting learners to plan, attend to relevant content, and monitor and evaluate their learning. This position paper sets out to inform policy makers,educators, researchers, and others of the importance of a metacognitive e-learning approachwhen designing instruction using Course Management Systems. Such a metacognitive approach will improve the utilization of CMSs to support learners on their path to self-regulation. We argue that a powerful CMS incorporates features and functionalities that can provide extensivescaffolding to learners and support them in becoming self-regulated learners. Finally, we believethat extensive training and support is essential if educators are expected to develop and implement CMSs as powerful learning tools.